x2-12x+36=64

Move 64 to the left side of the equation by subtracting it from both sides.

x2-12x+36-64=0

Subtract 64 from 36.

x2-12x-28=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -28 and whose sum is -12.

-14,2

Write the factored form using these integers.

(x-14)(x+2)=0

(x-14)(x+2)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x-14=0

x+2=0

Set the first factor equal to 0.

x-14=0

Add 14 to both sides of the equation.

x=14

x=14

Set the next factor equal to 0.

x+2=0

Subtract 2 from both sides of the equation.

x=-2

x=-2

The final solution is all the values that make (x-14)(x+2)=0 true.

x=14,-2

Solve Using the Square Root Property x^2-12x+36=64